2016
DOI: 10.5498/wjp.v6.i3.358
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and conversion formula between mini-mental state examination and montreal cognitive assessment in an outpatient sample

Abstract: AIMTo explore the agreement between the mini-mental state examination (MMSE) and montreal cognitive assessment (MoCA) within community dwelling older patients attending an old age psychiatry service and to derive and test a conversion formula between the two scales.METHODSProspective study of consecutive patients attending outpatient services. Both tests were administered by the same researcher on the same day in random order.RESULTSThe total sample (n = 135) was randomly divided into two groups. One to derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 29 publications
(35 reference statements)
3
23
0
1
Order By: Relevance
“…Equating the two scales is useful for interpreting follow-up results when each assessment was done with a different scale and for clinicians to become accustomed to the relatively newer assessment. The largest equated difference between both MoCA versions was four points in those scoring within 10-20 points on the MoCA-A, which was not as large as in studies that equated the original MoCA with the MMSE [ 15 , 21 , 50 , 51 ]. Additionally, the ceiling effect was much smaller than that seen when equating with the MMSE [ 15 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Equating the two scales is useful for interpreting follow-up results when each assessment was done with a different scale and for clinicians to become accustomed to the relatively newer assessment. The largest equated difference between both MoCA versions was four points in those scoring within 10-20 points on the MoCA-A, which was not as large as in studies that equated the original MoCA with the MMSE [ 15 , 21 , 50 , 51 ]. Additionally, the ceiling effect was much smaller than that seen when equating with the MMSE [ 15 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 74%
“…The largest equated difference between both MoCA versions was four points in those scoring within 10-20 points on the MoCA-A, which was not as large as in studies that equated the original MoCA with the MMSE [ 15 , 21 , 50 , 51 ]. Additionally, the ceiling effect was much smaller than that seen when equating with the MMSE [ 15 , 50 , 51 ]. The MMSE relies heavily on orientation and is less capable of detecting MCI in general [ 52 ].…”
Section: Discussionmentioning
confidence: 74%
“…To derive equivalence of MMSE to MoCA-30 and MoCA-22, and MoCA-30 to MoCA-22 total scores, we used the equipercentile equating method with log-linear smoothing [16][17][18][19][27][28][29][30]. This method equates scores from two measures based on the equivalency of their corresponding percentile ranks [31].…”
Section: Discussionmentioning
confidence: 99%
“…Until there is additional data to further delineate performance in the oldest-old, we suggest using total, rather than the age-groupspecific, subtest scores as a normative reference. We determined the equivalence of MMSE to MoCA-30 and MoCA-22, and MoCA-30 to MoCA-22 scores using the equipercentile equating method as was done in most studies [16][17][18][19][20][27][28][29][30]. We found that an MMSE score of 27 corresponds to a MoCA-30 score of 22, which is similar to other reports where MMSE score of 27 is equivalent to MoCA-30 scores of 21-24 [16-19, 27-30, 34-37].…”
Section: Equivalences Of Mmse Moca-30 and Moca-22 Scoresmentioning
confidence: 99%
“…Existen algunos estudios donde se comparan los puntajes del MoCA con los del MMSE y estos sugieren la existencia de algún grado de superioridad del primero en la detección del deterioro cognitivo leve, por lo que se ha convertido en una herramienta con diferentes validaciones internacionales 14,15 . Según Helmi et al, las dos pruebas son similares para evaluar la función cognitiva general haciendo énfasis en aspectos neuropsicológicos 16 .…”
unclassified